Weight Loss Medications in Young Adults after Bariatric Surgery for Weight Regain or Inadequate Weight Loss: A Multi-Center Study - Alexander T. Toth; Gricelda Gomez; Alpana P. Shukla; Janey S. Pratt; Hellas Cena; Ginevra Biino; Louis J. Aronne; Fatima Cody Stanford (MDPI AG, 2018)
This paper presents a retrospective cohort study of weight loss medications in young adults aged 21 to 30 following Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) between November 2000 and June 2014. Data were collected from patients who used topiramate, phentermine, and/or metformin postoperatively. Percentage of patients achieving ≥5%, ≥10%, or ≥15% weight loss on medications was determined and percent weight change on each medication was compared to percent weight change of the rest of the cohort. Our results showed that 54.1% of study patients lost ≥5% of their postsurgical weight; 34.3% and 22.9% lost ≥10% and ≥15%, respectively. RYGB had higher median percent weight loss (−8.1%) than SG (−3.3%) (p = 0.0515). No difference was found in median percent weight loss with medications started at weight plateau (−6.0%) versus after weight regain (−5.4%) (p = 0.5304). Patients taking medications at weight loss plateau lost 41.2% of total body weight from before surgery versus 27.1% after weight regain (p = 0.076). Median percent weight change on metformin was −2.9% compared to the rest of the cohort at −7.7% (p = 0.0241). No difference from the rest of the cohort was found for phentermine (p = 0.2018) or topiramate (p = 0.3187). Topiramate, phentermine, and metformin are promising weight loss medications for 21 to 30 year olds. RYGB patients achieve more weight loss on medications but both RYGB and SG benefit. Median total body weight loss from pre-surgical weight may be higher in patients that start medication at postsurgical nadir weight. Participants on metformin lost significantly smaller percentages of weight on medications, which could be the result of underlying medical conditions.